A simple microsatellite-based method for hazelnut oil DNA analysis. (15th April 2018) - Lucchetti, Sabrina; Pastore, Gianni; Leoni, Guido; Arima, Serena; Merendino, Nicolò; Baima, Simona; Ambra, Roberto
Highlights: Molecular analyses of hazelnut oil have been performed using SSRs. Silica column-based DNA extraction is preferable for hazelnut oil SSR analysis. SSRs used yielded identical molecular profiles in hazelnut oil and raw nuts. Abstract: Molecular food traceability requires continuous updates to identify more robust, efficient and affordable methodologies to guarantee food quality and safety and especially consumers' health. Available commercial kits are often unsatisfactory and require modifications to successfully detect single components on complex and transformed food matrices. Here we report a simple method for molecular traceability of cold-pressed hazelnut oil based on microsatellite DNA markers. Different genomic extraction methodologies were tested and a total genome pre-amplification step was applied on PCR-negative samples. PCR-capillary electrophoresis using nine microsatellites demonstrates the accuracy of the fingerprint analysis even for filtered oil.